ДІЛОВА ГРА ЯК ОДНА З ФОРМ МЕТОДИЧНОЇ РОБОТИ З РОЗВИТКУ ТВОРЧОГО СТИЛЮ ДІЯЛЬНОСТІ ПЕДАГОГА (Педагогіка вищої та середньої школи, 2004)
The point, the specificity, the ways, and the methods of organization of business games are based in this article during the methodical work like one of the forms of development of creative style in teacher's work.